The Point Cloud Semantic Segmentation Method for the Ming and Qing Dynasties’ Official-Style Architecture Roof Considering the Construction Regulations - Youqiang Dong; Yihao Li; Miaole Hou (ISPRS International Journal of Geo-Information, 2022)
Point cloud semantic segmentation has played an important role in the scan-to-BIM process of the Ming and Qing Dynasties’ official-style architecture roof. To overcome the complexity of roof components’ shape and the scale differences between different roof component types, a point cloud semantic segmentation method for the MQDOAs roof considering the construction regulations is proposed in this paper. This method is composed of two stages. In the first stage, the features from the construction rules of MQDOAs, including the normalized symmetrical distance (NSD), relative height (RH) and local height difference (LHD), are extracted alongside the regular geometric features. To lower the influence of scale differences, a multi-scale feature connection strategy is also applied to construct the feature classification vector. In the second stage, RF method is applied to classify the point cloud. To verify the efficiency of the proposed method, we took the Hall of Complete Harmony as the study case. The experiments showed that our method achieved segmentation result in overall classification accuracy and reached 96.8%.